1997
DOI: 10.1007/bf02316806
|View full text |Cite
|
Sign up to set email alerts
|

Multiple primary melanomas: Implications for screening and follow-up programs for melanoma

Abstract: Once individuals are diagnosed with melanoma, they are in a high-risk population for having other primary site melanomas diagnosed and should be placed in an intensive follow-up protocol consisting of a complete skin examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
1
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 15 publications
4
62
1
3
Order By: Relevance
“…3,6,7,9,12,[15][16][17][18][19][20] A study from the John Wayne Cancer Institute examined the first 2 primary melanomas in 114 patients with MPM who were identified from a melanoma database and demonstrated that there were significant differences between AJCC stage, mean tumor thickness, and Clark level of invasion between the first and second melanomas, and the second melanoma was thinner. 21 Our results indicating that the thickness of the first primary melanoma is significantly greater compared with the thickness of the second melanoma are consistent with previously reported findings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…3,6,7,9,12,[15][16][17][18][19][20] A study from the John Wayne Cancer Institute examined the first 2 primary melanomas in 114 patients with MPM who were identified from a melanoma database and demonstrated that there were significant differences between AJCC stage, mean tumor thickness, and Clark level of invasion between the first and second melanomas, and the second melanoma was thinner. 21 Our results indicating that the thickness of the first primary melanoma is significantly greater compared with the thickness of the second melanoma are consistent with previously reported findings.…”
Section: Discussionmentioning
confidence: 99%
“…21 Our results indicating that the thickness of the first primary melanoma is significantly greater compared with the thickness of the second melanoma are consistent with previously reported findings. Two hypotheses have been proposed to explain why subsequent melanomas in patients with MPM are thinner: 1) close surveillance of patients who had a previous melanoma, leading to the early detection of any additional melanomas 15,21,22 ; and 2) distinct tumor biology in MPM versus SPM, because melanomas in patients with MPM have less aggressive tumor biology than melanomas in patients with SPM. 12 The hypothesis that close surveillance of patients with melanoma may lead to thinner melanomas is supported by a recent retrospective study, which indicated that patients with MPM who received regular follow-up had thinner melanomas than those who were not followed regularly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Depending on tumor thickness, the majority of recurrences even in thin melanomas (< 1.0 mm), occurred within the first years after primary diagnosis [590,596,599]. The risk for recurrence after 10 years is roughly 1 % [588].…”
Section: Background Information On the Clinical Decision Processmentioning
confidence: 99%